2007
DOI: 10.1371/journal.pone.0001138
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Status in Ovarian Carcinomas: A Multicenter GINECO Study of 320 Patients

Abstract: BackgroundDespite a typically good response to first-line combination chemotherapy, the prognosis for patients with advanced ovarian cancer remains poor because of acquired chemoresistance. The use of targeted therapies such as trastuzumab may potentially improve outcomes for patients with ovarian cancer. HER2 overexpression/amplification has been reported in ovarian cancer, but the exact percentage of HER2-positive tumors varies widely in the literature. In this study, HER2 gene status was evaluated in a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
119
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(134 citation statements)
references
References 42 publications
10
119
1
4
Order By: Relevance
“…Inconsistent results have been published with respect to the HER2 expression but the most recent studies seem to agree that only a minority of ovarian cancer overexpress HER2 (9,18,24,25). This was also seen in our study where only a small group of the ovarian cancer patients showed 2+ or 3+ overexpression by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Inconsistent results have been published with respect to the HER2 expression but the most recent studies seem to agree that only a minority of ovarian cancer overexpress HER2 (9,18,24,25). This was also seen in our study where only a small group of the ovarian cancer patients showed 2+ or 3+ overexpression by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the numerous studies on the expression and clinical significance of HER1 (4-6) and HER2 (3,(7)(8)(9), the role of these receptors are still controversial in ovarian cancer. Furthermore, only few studies have described the tissue expression of the HER3 and HER4 receptor protein in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Three patients had cerbB2 2+ disease and, considering breast cancer pathology and HER2 positivity criteria, it would have been helpful to perform in situ hybridization techniques to evaluate HER2 gene amplification at least in these patients. Nevertheless, a previous study demonstrated that 100% of cerbb2 3+ cases were HER2 amplified, while only 25% of cerbB2 2+ cases were also FISH + (Tuefferd et al, 2007). Therefore, the lack of FISH analysis in this study is not a deficiency.…”
Section: Discussionmentioning
confidence: 61%
“…The prognostic role of HER2 overexpression in EOC remains unclear. Some studies proposed that an elevated HER2 level was associated with poorer survival (Lassus et al, 2004;Steffensen et al, 2007), whereas other studies could not demonstrate any association (Verri et al, 2005;Tuefferd et al, 2007). In the meta-analysis conducted by Zhao et al (2013), the prognostic effect of HER2 overexpression was also explored; after reviewing eight studies, they demonstrated that HER2 overexpression was significantly associated with poorer overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Her-2 is also a target for novel therapeutic approaches, such as trastuzumab, a recombinant antibody designed to block signaling through the Her-2 receptor. Her2 expression in ovca shows rates of 1.8-76%, but data related to its prognostic value are controversial (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%